Preparing short message service reminders to improve treatment adherence among tuberculosis patients in Sleman District, Indonesia - Fatwa Sari Tetra Dewi; Sudiya Sudiya; Supriyati Supriyati; Purwanta Purwanta; Ema Madyaningrum; Firda Ulfa Aulia; Risma Wardiani; Adi Utarini (Wolters Kluwer Medknow Publications, 2019)
Background: Modern tuberculosis (TB) treatment approaches require innovative adherence strategies. Objectives: This study aimed to explore the feasibility of using short message service (SMS) reminders through mobile phones to improve treatment adherence among TB patients. Materials and Methods: An exploratory sequential design was applied; initially, qualitative data collection was conducted among TB patients and TB program officers. A content analysis was done and messages were then developed. The messages were pretested using focus group discussions (FGDs), and a quantitative method using quasi-experiment on 120 TB patients. All the patients received a standard directly observed therapy short reminder, but only intervention group received daily SMS reminders (n = 60), the data were then analyzed using logistic regression. Results: Reminder messages can be sent directly to young TB patients or indirectly to the relatives of elderly patients. There are four phases of emotional states, which TB patients go through during treatment starting with disappointment and desperation after being diagnosed, grievance during the initiation of treatment, high and then low desire to follow treatment. Reminder messages aimed at improving treatment adherence should correspond to those conditions and motivate, inform, and facilitate TB patients to overcome all the obstacles during treatment. SMS reminders should also be short, informal, and easy to understand. Treatment adherence was significantly higher among the intervention group compared to the control group (odds ratio = 10.73) after controlling for demographics, accessibility, and adverse drug reaction. Conclusions: SMS through mobile phone is a feasible form of media to remind TB patients and to improve adherence to treatment in low-resource facilities.